Peran dan Fungsi Supervisi Pendidikan dalam Meningkankan Etos Kerja Guru dalam Pembelajaran - Azhar, Dzul; Hasan, Ismail; Fatimah, Meti (Lembaga Yasin AlSys, 2025)
This study explores the concept of educational supervision, focusing on its understanding, importance, objectives, functions, objects, and guiding principles. A qualitative research method was employed, supported by a library research approach, to provide a descriptive and contextual analysis. The study highlights the necessity for educational supervisors, principals and school supervisors to possess strong professional competencies in implementing instructional supervision. These professional abilities are crucial for enhancing the quality of teacher development in schools. Effective school supervision, guided by the principal's ability to responsibly execute their duties, aims to improve and advance teacher performance. By fostering professional growth, supervision ensures that teachers can fulfill their responsibilities with competence and integrity.